2003
DOI: 10.1046/j.1570-7458.2003.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketone components in the contact sex pheromone of the white‐spotted longicorn beetle, Anoplophora malasiaca, and pheromonal activity of synthetic ketones

Abstract: Two active fractions were found during the isolation of contact sex pheromone of female elytra of the white‐spotted longicorn beetle, Anoplophora malasiaca (Thomson) (Coleoptera: Cerambycidae), in addition to fraction of hydrocarbons that had previously been identified. One fraction was essential to evoke a series of precopulatory behaviors of males toward a glass dummy when coated together with the hydrocarbon blend. The other fraction enhanced this activity when added to the mixture. From the latter synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 7 publications
2
35
0
Order By: Relevance
“…In subfamily Lamiinae, female attraction by males was observed in Monochamus alternatus (Fauziah et al, 1987) and male-specific compounds were identified in Anoplophora glabripennis (Zhang et al, 2002). However, we have no behavioral evidence for female-or male-specific sex attractant pheromone released by females or males in Psacothea hilaris (Pascoe) (Fukaya and Honda, 1992, 1995, 1996aFukaya et al, 1996Fukaya et al, , 1997Fukaya, 2004) and A. malasiaca (Fukaya et al, 1999(Fukaya et al, , 2000(Fukaya et al, , 2004a(Fukaya et al, , b, 2005aAkino et al, 2001;Yasui et al, 2003). In a previous study, we reported that the male elytra extracts facilitate female mate location before contact (Fukaya et al, 2005b).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In subfamily Lamiinae, female attraction by males was observed in Monochamus alternatus (Fauziah et al, 1987) and male-specific compounds were identified in Anoplophora glabripennis (Zhang et al, 2002). However, we have no behavioral evidence for female-or male-specific sex attractant pheromone released by females or males in Psacothea hilaris (Pascoe) (Fukaya and Honda, 1992, 1995, 1996aFukaya et al, 1996Fukaya et al, , 1997Fukaya, 2004) and A. malasiaca (Fukaya et al, 1999(Fukaya et al, , 2000(Fukaya et al, , 2004a(Fukaya et al, , b, 2005aAkino et al, 2001;Yasui et al, 2003). In a previous study, we reported that the male elytra extracts facilitate female mate location before contact (Fukaya et al, 2005b).…”
Section: Discussionmentioning
confidence: 84%
“…The white-spotted longicorn beetle Anoplophora malasiaca (Thomson) (Coleoptera: Cerambycidae: Lamiinae) is a serious pest of citrus, and mating behavior has been intensively studied (Fukaya et al, 1999(Fukaya et al, , 2000(Fukaya et al, , 2004a(Fukaya et al, , b, 2005aAkino et al, 2001;Yasui et al, 2003). When a male encounters a female, he holds and mounts her back and then usually attempts to bend his abdominal tip towards her abdomen (Fukaya et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding in A. malasiaca, that the blending of cuticular hydrocarbons and polar components is essential to reveal the pheromonal activity had not been reported in other longicorn beetles (our study is the only one in the world to provide an analysis of the contact pheromone in the longicorn beetle). We detected 2 or more groups of pheromonally active components, and the identification of their chemical structure is in progress (Recently 4 ketone compounds have been identified: Yasui et al, 2003) 23 .…”
Section: Polar Components Of Contact Pheromone In Anoplophora Malasiacamentioning
confidence: 99%
“…The female white-spotted longicorn beetle Anoplophora malasiaca (Thomson) (Coleoptera: Cerambycidae, Lamiinae) produces a sex pheromone on her body and evokes sequential copulating behaviors in males through direct contact with antennae, palpi, or tarsi (Fukaya et al, 1999(Fukaya et al, , 2000Akino et al, 2001;Fukaya, 2003;Yasui et al, 2003). Recently, we reported that a female volatile chemical mediates short distance mate location in A. malasiaca by males, and that visual stimuli in association with female substances are also involved (Fukaya et al, 2004).…”
Section: Introductionmentioning
confidence: 99%